2014
DOI: 10.1007/s11230-013-9466-z
|View full text |Cite
|
Sign up to set email alerts
|

Four new coccidia (Apicomplexa: Eimeriidae) from the Plateau zokor, Myospalax baileyi Thomas (Rodentia: Myospalacinae), a subterranean rodent from Haibei area, Qinghai Province, China

Abstract: Thirty-eight faecal samples from the Plateau zokor, Myospalax baileyi Thomas, collected in the Haibei Area, Qinghai Province, China, were examined for the presence of coccidia (Apicomplexa: Eimeriidae). Seventeen of 38 faecal samples (44.7%) were found to contain coccidian oöcysts representing four new species of Eimeria Schneider, 1875, and four of 17 (23.5%) infected zokors were concurrently infected with two or three of these eimerian species. The sporulated oöcysts of Eimeria myospalacensis n. sp. are ovoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“… Cao et al (2014) described four new species of Eimeria from the Plateau zokor, Eospalax baileyi , collected from Haibei area, Qinghai Province, China. The parasites include Eimeria baileyii Cao et al, 2014 , Eimeria fani Cao et al, 2014 , Eimeria menyuanensis Cao et al, 2014 , and Eimeria myospalacensis Cao et al, 2014 . In the same year, Zhao et al (2014) identified Versteria (syn.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Cao et al (2014) described four new species of Eimeria from the Plateau zokor, Eospalax baileyi , collected from Haibei area, Qinghai Province, China. The parasites include Eimeria baileyii Cao et al, 2014 , Eimeria fani Cao et al, 2014 , Eimeria menyuanensis Cao et al, 2014 , and Eimeria myospalacensis Cao et al, 2014 . In the same year, Zhao et al (2014) identified Versteria (syn.…”
Section: Resultsmentioning
confidence: 99%
“…Eimeria faniCao et al, 2014Cao et al 2014 Eimeria menyuanensisCao et al, 2014Cao et al 2014 Eimeria myospalacensisCao et al, 2014Cao et al 2014 Ransomus qinghaiensisMing et al, 2004Ming et al 2004 Versteria (syn. Taenia) mustelae Gmelin, 1790 Zhao, et al 2014Heligmonina nevoiNevo, 1971 Wertheim andNevo 1971 Isospora spalacensisCouch et al, 1993Couch et al 1993 Microcephaloides nevoi(Fair et al, 1990) Haukisalmi 2009Fair et al 1990Haukisalmi 2009 Trichuris muris (Schrank, 1788)Wertheim and Nevo 1971 …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to some terrestrial rodents, plateau zokors are less active, and their unique geographic location and living habits make them often an ideal model for studying phenotypic and ecological adaptations ( Kang et al, 2020b ). This also leads to a low probability of exogenous anthropogenic influences and pathogen invasion in plateau zokors, and intra-population intestinal parasites may be more likely to occur to produce host-adapted genotypes ( Cao et al, 2014 ; Zhao et al, 2014 ). Therefore, we investigated the infection status of plateau zokors with Cryptosporidium spp., E. bieneusi , G. lamblia and B. hominis on the Tibetan plateau.…”
Section: Introductionmentioning
confidence: 99%